Is Corporate Governance an HR Responsibility?. Issue 4 (October 2019) - Busrai, Aquil
Abstract: Often there is a question about who owns responsibility for corporate governance. Is it only the CEO's responsibility or is it the responsibility of HR function? Busrai provides a holistic view of how HR can, and should, play as a guardian angel in the organisation to maintain high level of governance and ethics. A refreshing viewpoint that raises HR's contribution to a new level in the organisation.